Comparison of Microstructural and Morphological Properties of Electrodeposited Fe-Cu Thin Films with Low and High Fe : Cu Ratio - Umut Sarac; M. Celalettin Baykul (Advances in Materials Science and Engineering)
Fe-Cu films with low and high Fe : Cu ratio have been produced from the electrolytes with different Fe ion concentrations at a constant deposition potential of −1400 mV versus saturated calomel electrode (SCE) by electrodeposition technique onto indium tin oxide (ITO) coated conducting glass substrates. It was observed that the variation of Fe ion concentration in the electrolyte had a very strong influence on the compositional, surface morphological, and microstructural properties of the Fe-Cu films. An increase in the Fe ion concentration within the plating bath increased the Fe content, consequently Fe : Cu ratio within the films. The crystallographic structure analysis showed that the Fe-Cu films had a mixture of face-centered cubic (fcc) Cu and body centered cubic (bcc) α-Fe phases. The average crystallite size decreased with the Fe ion concentration. The film electrodeposited from the electrolyte with low Fe ion concentration exhibited a morphology consisting of dendritic structures. However, the film morphology changed from dendritic structure to cauliflower-like structure at high Fe ion concentration. The surface roughness and grain size were found to decrease significantly with increasing Fe ion concentration in the electrolyte. The significant differences observed in the microstructural and morphological properties caused by the change of Fe ion concentration in the electrolyte were ascribed to the change of Fe : Cu ratio within the films.